Urban Geochemical Hazard Mapping of St. John’s, Newfoundland, Canada - Foley, Robert; Bell, Trevor; Liverman, David (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 2011)
ABSTRACT The surface soil concentrations (n = 997) of ten metals with Canadian Council of Ministers of the Environment soil quality guidelines were mapped on residential properties in the City of St. John’s, Newfoundland and Labrador, Canada. Concentrations of all metals are elevated above background levels, five of the ten metals – As, Ba, Cu, Pb, and Zn – have concentrations above environmental health guidelines in more than 20% of samples, and three metals – As, Pb, and V – exceed human health guidelines in 34 to 47% of samples. Using a contamination index, surface soil was shown to be highly contaminated in the downtown area, primarily on residential properties predating the 1950s. In order of influence, the four metals with the highest contamination factor are Pb, Zn, As, and Cu. Compared to background levels, surface soils are significantly enriched in Pb and Cd, and moderately enriched in Cr, Cu, and Zn. A hierarchical clustering procedure indicated strong statistical relationships between the occurrences of two metal groups across all soil samples. One group – Pb-Zn-Cd – has consistently elevated concentrations in soil sampled adjacent to the exterior walls of buildings, although high values were also recorded in roadside sites and from open spaces on properties. The second group – Cr-Ni-Cu – has minimal to moderately elevated concentrations in all sample locations, though slightly higher concentrations along roadsides. The clusters of metals and their spatial concentration patterns suggest that weathered paint, vehicular emissions, and coal burning were important sources for the main contaminants in sampled soils. Of the three metals (i.e., As, Pb, and V) which significantly exceed human health guidelines, Pb and As pose the greatest potential health risk and require further assessment. It is possible that other cities in the region that share similar urban history and characteristics have a potentially hazardous geochemical landscape.